Synthesis of strong magnetic response ZIF-67 for rapid adsorption of Cu2+ - Lei, Yuanhang; Yang, Haibo; Xie, Jiangqin; Chen, Qi; Quan, Wenxuan; Wang, Anping (Frontiers in Chemistry, 2023)
With the acceleration of industrialization and urbanization, global water resources have been polluted. Among the water pollutants, heavy metals have caused great harm to the environment and organisms. When the concentration of Cu2+ in water exceeds the standard, the intake of the human body will mainly damage the nervous system. We use MOF materials with high chemical stability, specific surface area, adsorption, and other unique properties to adsorb Cu2+. MOF-67 was prepared with various solvents, and a stronger magnetic response MOF-67 with the largest surface area and best crystal form were selected. It quickly adsorbs low-concentration Cu2+ in water to purify water quality. At the same time, it can be recovered promptly through an external magnetic field to avoid secondary pollution, which conforms to the concept of green environmental protection. When the initial concentration of Cu2+ is 50 mg/L for 30 min, the adsorption rate reaches 93.4%. The magnetic adsorbent can be reused three times.